Well-defined mesoporosity on lignocellulosic-derived activated carbons. - Silvestre-Albero, Ana; Goncalves, Maraisa; Itoh, Tsutomu; Kaneko, Katsumi; Endo, Morinobu; Thommes, Matthias; Rodriguez-Reinoso, Francisco; Silvestre-Albero, Joaquin (Carbon, 2012)
Activated carbons with a highly developed mesoscale cavitation-linked structure were prepd. from natural products (e.g. peach stones) by combining chem. and phys. activation processes. Characterization results show that these materials exhibit a large "apparent" surface area (∼1500 m2/g) together with a well-defined mesoporous structure, i.e. large cavities connected to the external surface through narrower mesoporous necks (cavitation effects). [on SciFinder(R)]
Keywords: activated carbon lignocellulosic derived mesoporosity